Clinical Long-Term Complications of Post Covid Time in Patients Reporting at PAF Hospital Within 3 Months After Discharge - Mehtab, Javaria; Niaz, Asif; Azhar, Nabeeha; Khawaja, Mahnoor (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the long term complications of post COVID time in patients reporting within 3 months after discharge. Study design: Cross-sectional study. Place and duration of study: Department of Medicine, PAF Hospital, Islamabad. From July 2021 to June 2022. Methods: A total of 100 patients, ≥ 18 years of age, with a confirmed diagnosis of COVID-19 infection and admission to the hospital, presenting to the outpatient department within 3 months of hospital discharge were enrolled in this study. All the related demographics were noted and details of medical history was taken from patient’s medical record. Clinical symptoms were recorded using a standard questionnaire and grouped as respiratory, musculoskeletal, cardiovascular, neurological, gastrointestinal and psychological functions to determine the full spectrum of post-COVID sequelae. Results: Mean age of patients in this study was 53.88±8.03 years with an age range of 39 to 67 years. Males were 57% of total study population while females were 43%. The details of clinical symptoms reported by these patients showed that fatigue (59%), dyspnea (47%) and loss of taste/smell (41%) were the most frequent symptoms reflecting COVID-19 complications associated with musculoskeletal, respiratory and neurological functions. Conclusion: COVID-19 patients reporting within 3 months of discharge from hospitalization still experience fatigue, dyspnea, and loss of taste/smell, indicating respiratory, musculoskeletal and neurological complications even after recovery from this infection.